2015
DOI: 10.1179/1465313314y.0000000122
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Tanaka–Johnston and Moyers mixed dentition analyses in Northeast Han Chinese

Abstract: Both the Tanaka-Johnston and Moyers method may not be applied universally without question. Hence, it may be safer to develop regression equations for specific populations. Validating studies must be conducted to confirm the precision of these newly developed regression equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Coefficient of determination (r 2 ) in our study ranged between 0.41 and 0.63 suggesting that 41 to 63% of the total variation in the sum of mesiodistal widths of unerupted canine and premolars (y) can be explained by the sum of mesiodistal widths of mandibular incisors (x). The r 2 values of our study were comparable to that of Nepalese Brahmins/Chhetris [18] and Hong Kong Chinese [11] but higher when compared to Han Chinese [12], Saudi Arabian [31], Senegalese [22], Thai [15] and Syrian [16] population. However, studies conducted in Turkey [30] and Uganda [24] have reported higher r 2 values than our study.…”
Section: Discussionsupporting
confidence: 75%
“…Coefficient of determination (r 2 ) in our study ranged between 0.41 and 0.63 suggesting that 41 to 63% of the total variation in the sum of mesiodistal widths of unerupted canine and premolars (y) can be explained by the sum of mesiodistal widths of mandibular incisors (x). The r 2 values of our study were comparable to that of Nepalese Brahmins/Chhetris [18] and Hong Kong Chinese [11] but higher when compared to Han Chinese [12], Saudi Arabian [31], Senegalese [22], Thai [15] and Syrian [16] population. However, studies conducted in Turkey [30] and Uganda [24] have reported higher r 2 values than our study.…”
Section: Discussionsupporting
confidence: 75%
“…Once the prediction size of the unerupted permanent teeth is found, the most likely degree of crowding can be established 7 . Early diagnosis and interception of crowding undoubtedly aids in better treatment planning to tackle crowding and thereby the effects produced by it [8][9][10] . The severity of malocclusion in the future can be markedly decreased using timely interception.…”
Section: Introductionmentioning
confidence: 99%
“…This results is similar to conclusions of other studies that indicated inacuracy of moyer prediction tables for females. (32,33) Further studies are reguired to test the accuracy of prediction tables at 50 th percentile for the egyption population…”
Section: Discussionmentioning
confidence: 99%